Analysis of a Gas Turbine Plant for Distributed Power Cogeneration Along with Heating, Refrigeration and Air Conditioning. Issue 2 (1st March 2017) - Subbarao, Rayapati; Sarath, K. Sai
ABSTRACT: Gas turbine plants play important role in power production whenever there has been scarcity of power generated from conventional sources like oil or gas. Researchers have been trying to simulate this kind of power plants for higher outputs with improved system efficiency. In this scenario, present work attempts to study and simulate a closed cycle gas turbine power plant for different configurations. All the components are modelled and integrated to form a power generating and heating system. Parameters like compressor inlet pressure, pressure ratio and turbine inlet temperature are varied. Performance curves of the individual components and the integrated system are plotted and studied. Results obtained show the significance of pressure ratio and turbine inlet temperature. Utilization of heat from turbine exhaust shows the possibility of a cogeneration bottoming cycle that can be used for district heating, refrigeration and air conditioning applications. Also, it is found that inlet pressure of 1 bar allows both topping and bottoming cogeneration cycles to perform optimally.